Implementasi Metode Promethee dalam Penentuan Penerima Bantuan Zakat pada Mahasiswa - Rima Aprilia; Rina Widyasari (CESS (Journal of Computer Engineering, System and Science), 2021)
During the payment of a single tuition fee (UKT) every semester, students are always faced with the problem of outstanding students but unable to pay tuition fees. Therefore, the university provides a solution to give zakat obtained from lecturers to outstanding and underprivileged students through the selection process. So far, the student selection process is still done manually, not using a system or program. So that the distribution of educational aid recipients (zakat) is considered not on target. This will certainly be a continuous problem of injustice, especially now that we have entered the digital era 4.0, all processes use a digital system. The provision of educational fund assistance in the form of zakat must be based on established rules, in this case the rules are in the form of established criteria, namely student IP, parental income, number of siblings, number of dependents of parents, semester, and others. The purpose of this study is to test whether the Promethee method is a method that can solve these problems. In addition, this research also forms a flow chart for selecting recipients of educational assistance using the Promethee method. The results of this study indicate that the problem of determining recipients of zakat assistance by students can be solved using the PROMETHEE method. Promethee (Preference Ranking Organization for Enrichment Evaluation), This method is appropriate for determining recipients of zakat assistance.